Актуальні питання організації облікової політики у закладах вищої освіти: проблематика сьогодення - Атамас, Олександр Петрович; Atamas, Oleksandr (Науково-освітній інноваційний центр суспільних трансформацій м. Чернігів, 2023)
У статті проаналізовано роль облікової політики, розглянуто комплекс проблем формування та проведення облікової політики на платформах закладів вищої освіти та розкрито шляхи вирішення актуальних проблем сьогодення, які пов’язані із організацією облікової політики у закладах вищої освіти. В контексті проведеного дослідження проаналізовано термін «облікова політика» у відповідності із Законом України «Про бухгалтерський облік та фінансову звітність» та Міжнародними стандартами бухгалтерського обліку. У дослідженні розкрито та охарактеризовано систему принципів, за якими заклади вищої освіти в Україні складають щорічну облікову звітність, провадять облікову політику на своїх платформах та впроваджують кращі світові практики у своїй діяльності. Крім того, у матеріалах статті проаналізовано вплив облікової політики на фінансову стійкість закладів вищої освіти, запропоновано комплекс рекомендацій щодо вдосконалення облікової політики та впровадження закордонного досвіду в Україні. The article analyzes the role of accounting policy, considers the set of problems of forming and implementing accounting policy on the platforms of higher education institutions, and reveals the ways to solve current problems related to the organization of accounting policy in higher education institutions. In the context of the research, the term «accounting policy» was analyzed in accordance with the Law of Ukraine «On Accounting and Financial Reporting» and International Accounting Standards. The study revealed and characterized the system of principles by which higher education institutions in Ukraine prepare annual accounting reports, conduct accounting policies on their platforms, and implement best global practices in their activities. In addition, the article analyzes the impact of accounting policy on the financial stability of higher education institutions, offers a set of recommendations for improving accounting policy and implementing foreign experience in Ukraine. Globalization transformations in the economy of Ukraine form qualitatively new priorities for the sustainable development of accounting policy on the platforms of higher education institutions. In particular, the complex of fundamental factors of the external and internal environment, which have an impact on the formation of accounting policy, its priorities and development, needs to be expanded and detailed. Since education is the key to innovation, transformational changes, SMART-development of the national economy, accounting policy in this area is an urgent issue of our time, forming the prerequisites for overcoming crisis phenomena and ways to improve economic changes. The issue of the organization of accounting in institutions of higher education becomes of primary importance and becomes an urgent problem of ensuring sustainable economic development on Ukraine’s path to European integration processes and the international practice of corresponding changes. Thus, the formation and development of accounting policy in institutions of higher education is a prerequisite for the development of not only the field of education, but also the direct improvement of the state of economic processes and the development of the competitiveness of country’s economy.
Actual issues of accounting policy organization in institutions of higher education: today’s issues
Keywords: облікова політика; accounting policy; освіта; education; імплементація; implementation; проблема; problem; організація; organization; формування; formation; аналіз; analysis